Engaging employers in apprenticeship opportunities : [making it happen locally] - (:unkn) unknown (OECD Publishing, 2017)
"This joint OECD-ILO publication provides guidance on how local and regional governments can foster business-education partnerships in apprenticeship programmes and other types of work-based learning, drawing on case studies across nine countries. There has been increasing interest in apprenticeships which combine on the job training with classroom-based study, providing a smooth transition from school to work. There are benefits to both individuals and employers from participating in apprenticeships, including increased productivity and job quality. Successful implementation is contingent on having a high level of employer engagement at the local level, notably in the design, development and delivery of programmes." (Editor, BIBB-Doku)
Keywords: I 1 Internationale Berufsbildung; S 1 Stufen der Berufsbildung; Berufsbildungspolitik; Berufsausbildung; Betrieb; Ausbildungsplatzförderung; Programm; Best practice; Regionale Kooperation; OECD; Großbritannien; Norwegen; Bundesrepublik Deutschland; Australien; Neuseeland; USA; Türkei; Bangladesch; Indien